2008
DOI: 10.2139/ssrn.1095222
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Successful Exporter?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
(21 reference statements)
0
9
0
2
Order By: Relevance
“…Arkolakis and Muendler () find a positive association between the number of varieties exported and the destination country's market size). Due to the dynamic nature of exporting, firms' product mix changes, as product characteristics and firm characteristics change (Görg et al ., ). For example, Manova and Zhang () find that as firms become more able, they tend to focus on exporting higher quality (more expensive) products and dropping cheaper export products, as the former results in higher revenues.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Arkolakis and Muendler () find a positive association between the number of varieties exported and the destination country's market size). Due to the dynamic nature of exporting, firms' product mix changes, as product characteristics and firm characteristics change (Görg et al ., ). For example, Manova and Zhang () find that as firms become more able, they tend to focus on exporting higher quality (more expensive) products and dropping cheaper export products, as the former results in higher revenues.…”
Section: Literature Reviewmentioning
confidence: 97%
“…firms will export their top performing products to a more competitive market (Mayer et al 2011)); and market size (e.g., Arkolakis and Meundler (2010) find a positive association between the number of varieties exported and the destination country's market size). Due to the dynamic nature of exporting, firms' product mix changes, as product characteristics and firm characteristics change (Görg et al 2008). For example, Manova and Zhang (2012) find that as firms become more able, they tend to focus on exporting higher quality (more expensive) products and dropping cheaper export products, as the former results in higher revenues.…”
Section: Exportersmentioning
confidence: 99%
“…Besedeš and Prusa (2006b) found that in the case of US import trade relationships, the hazard rate was at least 18 per cent higher for homogenous goods than for differentiated goods. Görg et al (2008) showed that firms with higher quality products are able to remain more competitive in international markets, and hence their export duration is longer. Unfortunately, from our database, we do not have a good measure to capture the heterogeneous characteristics of exports.…”
Section: The Choice Of Variables and Data Issuesmentioning
confidence: 99%